Cholesterol Efflux Capacity and Cardiovascular Disease: The Ludwigshafen Risk and Cardiovascular Health (LURIC) Study - Andreas Ritsch; Angela Duerr; Patrick Kahler; Monika Hunjadi; Tatjana Stojakovic; Guenther Silbernagel; Hubert Scharnagl; Marcus E. Kleber; Winfried März (Biomedicines, 2020)
(1) Background and Aims: Efforts to reduce coronary artery disease (CAD) by raising high-density lipoprotein (HDL) cholesterol (HDL-C) have not been uniformly successful. A more important factor than HDL-C may be cellular cholesterol efflux mediated by HDL, which has been shown to be associated with CAD. In this report, we analyzed the influence of cardiovascular biomarkers and risk factors on cholesterol efflux in a prospective observational study of patients referred to coronary angiography. (2) Methods: HDL-mediated efflux capacity was determined for 2468 participants of the Ludwigshafen Risk and Cardiovascular Health (LURIC) study who were referred to coronary angiography at baseline between 1997 and 2000. Median follow-up time was 9.9 years. Primary and secondary endpoints were cardiovascular and all-cause mortality, respectively. (3) Results: Cholesterol efflux strongly correlated with HDL-related markers including HDL cholesterol, HDL phospholipids, and apolipoproteins AI and AII, as well as HDL particle concentration, which was not seen for low density lipoprotein (LDL) markers including LDL cholesterol and apoB. Cholesterol efflux was associated negatively with C-reactive protein (CRP), fibrinogen, interleukin-6 (IL-6), and serum amyloid A. Cardiovascular mortality was higher in patients in the lowest cholesterol efflux quartile. This association was weakened, but not fully abolished, after adjustment for HDL cholesterol. (4) Conclusions: We demonstrate that cholesterol efflux was associated with HDL-composition as well as inflammatory burden in patients referred for coronary angiography, and that this inversely predicts cardiovascular mortality independently of HDL cholesterol.